(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Political parties play an important role in organizing political life in different democratic systems because of their great ability to organize, educate, educate and train the different political groups of professional, trade union and student organizations. The internationalization of democracy in any political system through its acceptance of the existence of political parties cannot be a democracy without political parties. Political parties are one of the most important institutions of the political system specialized in political work, which seek to overcome underdevelopment and achieve development and modernization, where parties play a major role in the process of democratization and legitimizing the system of government through its efforts to get the masses to participate in the selection process Political leaders or through the integration of citizens in political life and instill democratic values ​​among them and raise their political awareness.